Fiat money: From the current Islamic finance scholars’ perspective - Jaffar, Syammon; Abdullah, Adam; Mydin Meera, Ahamed Kameel (Emerald Group Publishing Ltd., 2017)
Purpose: This paper aims to discuss the opinions of current Shariah scholars on the concept of debt money in the present-day fiat money system. Design/Methodology/Approach: This paper is a quantitative investigation of the opinions of Shariah experts, who were approached to answer our questionnaire. As a majority of Shariah scholars are also Shariah advisors to the current banking system, we felt that it was important to find out their levels of knowledge concerning the issue of debt money as it is created by the commercial banking sector’s fractional-reserve banking (FRB) system. Findings: Based on this investigation, most Shariah scholars are unaware of and confused about the mechanics underpinning the creation of money, especially with respect to FRB as it is practiced by the conventional and Islamic banking systems. Originality/Value: Based on this research, it is recommended that these scholars should improve their understanding of the operation of the fiat money system and its consequences. It is recommended that, in future, Shariah scholars should think ‘outside of the box’ by creating Islamic financial instruments that do not resemble those of the conventional system.